Perception of Thai Students about Graduate Business Program: Comparison between Online and On-Campus Program - Rojanadilok, Thanisorn; Daraviroj, Viroj (Information Management and Business Review, 2019)
This study was an investigation of the perception of Thai students on graduate business program comparison between Online and On-Campus program. The graduate business program appropriate with people who seek to advance your current position, growth your career, the source of competitive advantage, develop the business knowledge, development yourself, increase management skill, and start students’ own business. The qualitative research by in-depth interview of thirty students who want to study in graduate business in the comparison between Online and On-Campus program. The question was an interview about the benefit of Online and On-Campus business program, the disadvantage of Online and On-Campus business program, the balancing of learning ,working, life balance, the advance on job career of Online and On-Campus business program. The Online business program, students, can balance the learning, and work responsibility because of the graduate business program available to students 24 hours in 7 days in everywhere your convenience. The students can schedule, ask the question a one- on one meeting discussion between students, and professor. The Online program is not disrupting work, your hobby, and daily family life. The online graduate business program appropriates with people who seek to growth, your career and develop the business knowledge. The On-Campus program has a strong relationship, the connection among students more than the online graduate business program. Students can interact with friends and professor. On-Campus enhances the leadership of the students and quantitative skill. The student has alumni, and community in the building. On-Campus graduate business program appropriate with people who seek to advance your current position source of competitive advantage, increase management skill start students’ own business because program give the educational experience, and communication skill.